Surgical Options for Calcaneal Bony Defects: Current Clinical Evidence - Jong M Lee; Richard Buckley; Andrew Clark; Colin Drury; Christopher Del Balso; Amir Khoshbin; Timothy Daniels; Mansur Halai (Journal of Foot and Ankle Surgery (Asia Pacific))
Autografts, allografts, bone graft substitutes, and bone replacement materials have been utilized in isolation or in combination to fill bony defects and enhance fracture healing or arthrodesis in all subspecialties of orthopedics. Although there is a robust literature on the effect of bone grafts on managing large bone defects in long bones and arthrodesis, little has been published on the management of calcaneal bony defects. In this review, we aim to discuss the various options for calcaneal bony defects and the current clinical evidence behind each graft option.